2016
DOI: 10.1021/acs.jpca.6b04221
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Investigation on CrCun Clusters with n = 9–16: Noble Gas and Tunable Magnetic Property

Abstract: A systematic investigation on structure, dissociation behavior, chemical bonding, and magnetic property of Cr-doped Cun clusters (n = 9-16) is carried out using the mean of density functional theory calculations. It is found that CrCu12 is a crucial size, preferring an icosahedral Cu12 cage with the central Cr dopant. Smaller cluster sizes appear as on the way to form the CrCu12 icosahedron while larger ones are produced by attaching additional Cu atoms to the CrCu12 core. The presence of Cr dopant obviously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…We have recalculated the optimized geometries of Cu n Cr clusters (n = 9-11) using the BP86 functional with the basis sets cc-pvTZ-pp for Cu atom and cc-pvTZ for Cr atom to confirm the results presented in Ref. [23]. The previous investigation on ScCu n clusters also indicated that results obtained by the BP86 functional are well-matched to experimental values [21].…”
Section: Methodssupporting
confidence: 71%
See 4 more Smart Citations
“…We have recalculated the optimized geometries of Cu n Cr clusters (n = 9-11) using the BP86 functional with the basis sets cc-pvTZ-pp for Cu atom and cc-pvTZ for Cr atom to confirm the results presented in Ref. [23]. The previous investigation on ScCu n clusters also indicated that results obtained by the BP86 functional are well-matched to experimental values [21].…”
Section: Methodssupporting
confidence: 71%
“…As one should be agreed that the Cu n Cr clusters (n = 9-11) possess a certain spin states. In the previous work [23], the results went to the same conclusion that the studied clusters exhibit a magnetic moment but the question about their magnetic origin has not been understood completely yet. By knowing where the unpaired electrons locate, in this report we could prejudge by our physical intuition that the unpaired electrons are on the 3d orbitals of Cr atom.…”
Section: Electronic and Magnetic Propertiessupporting
confidence: 54%
See 3 more Smart Citations